2007
DOI: 10.1016/s0030-6657(07)70465-1
|View full text |Cite
|
Sign up to set email alerts
|

Niedosłuch czuciowo-nerwowy jako następstwo zatrucia tlenkiem węgla

Abstract: The authors describe the case of acute carbon monoxide intoxication in a 19 year old female patient, which caused, among other symptoms, bilateral sensorineural hearing loss. The symptoms, diagnostic methods and treatment with a particular regard to audiological examination were presented. Pathomechanism of carbon monoxide intoxication was also discussed. Despite the treatment, the effects of therapy have not been satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…If it is reversible, improvement is observed first in low frequencies [9]. Consistent with the findings of Pillion [13] and Skrzypczak et al [14], we observed a bilateral, high-frequency sensorineural hearing loss, and considering TEOAEs, the location of injury was in the outer hair cells. Nevertheless, in a case reported by Lee et al, hearing loss involved all frequencies except for 4 KHz [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…If it is reversible, improvement is observed first in low frequencies [9]. Consistent with the findings of Pillion [13] and Skrzypczak et al [14], we observed a bilateral, high-frequency sensorineural hearing loss, and considering TEOAEs, the location of injury was in the outer hair cells. Nevertheless, in a case reported by Lee et al, hearing loss involved all frequencies except for 4 KHz [8].…”
Section: Discussionsupporting
confidence: 90%
“…Unlike our patient and the cases reported by Pillion [13] and Skrzypczak et al [14], hearing loss after CO poisoning has been reported to revert by Lee et al [8], Shahbaz Hassan et al [18], Razzaq et al [15], and Michalska-Piechowiak et al [16]. In line with other similar cases [8, 11], our patient has never complained of tinnitus or vertigo.…”
Section: Discussionsupporting
confidence: 86%